A Comparative Evaluation Of Ascorbic Acid, Crude Fibre And Antioxidant Properties Of Selected Citrus Species Collected From Kanyakumari District (International Journal of Environmental Sciences, 2025)
Citrus fruits belong to the “Rutaceae” family, and are cultivated globally in tropical and subtropical regions with an approximate production of 102 million tons per year. They contain large quantities of vitamin C as well as appreciable amounts of several other nutrients such as minerals, vitamins, micronutrients, and dietary fibres. Citrus fruits are considered as one of the natural resources of antioxidants, which contain an appreciable amount of ascorbic acid, flavonoids, and phenolic compounds. The regular consumption of citrus fruits by humans has been associated with lower incidence of chronic-degenerative diseases, especially those mediated by free radicals. Most of the health-promoting properties of citrus fruits derive from their antioxidant content of carotenoids and ascorbic acid (ASC). In the present study, we have chosen three Citrus species viz., Citrus sinensis, Citrus japonica and Citrus depressa prevalently available in Kanyakumari District. Generally Citrus species consists of higher Ascorbic acid content so here we have selected three species to compare its ascorbic acid, crude fibre and antioxidant property. In the present study, the ethanolic extract of the whole fruit of these selected Citrus species were studied to find out the total ascorbic acid and crude fibre present in the selected Citrus species. The antioxidant activities were assessed and compared by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging effect. The results reported that compared to the three Citrus species, Citrus japonica revealed the higher Vitamin C, Crude fibre and Antioxidant property.